Marginality: Addressing the nexus of poverty, exclusion and ecology - Joachim von Braun; Franz W. Gatzweiler (Springer Open, 2014)
This volume presents new insights on marginality, i.e. the situation of people living on the edge of socio-economic and ecological systems. The marginality concept leads to different development policies. While the prevalence of poverty declined by about 50 percent in the past two decades, any further reduction of poverty will be more difficult, because of high diversity of extremely poor people, and complex interrelations between poverty, exclusion and ecology. The marginality concept provides guidance to address this issue. Marginality entails addressing the structural forces of poverty, such as exclusion, discrimination and ecological degradations which lead to vulnerability of the poor. In this volume economists, ecology experts, geographers, agronomists, sociologist, and business experts come together to address marginality. The inter-disciplinary research offers conceptual innovations and presents the dimensions of marginality in developing countries. Economic, political, and environmental drivers are assessed and mapped globally and in detail for countries in Africa and Asia, especially Ethiopia, India, Bangladesh, China, Indonesia. Economic growth especially in rural areas remains and farming communities is central to poverty reduction but needs to be complemented with specific actions to reach those at the margins. The social policy actions and measures to end exclusions are highlighted, and the roles of the state, local government, business and community in them are pointed out for overcoming marginality.
Keywords: 330; Developing countries; Development; Environmental changes; Marginalization; Poverty; Soziale Integration; Armut; Soziale Ungleichheit; Welt